Quality and User Satisfaction of SIMPADU in Business English Study Program of Languages and Literature Faculty of Universitas Negeri Makassar, Indonesia - Riny Jefri; Ansari Saleh Ahmar (Quantitative Economics and Management Studies, 2023)
This study aims to examine the effect of system quality seen from reliability, ease of use, flexibility and functionality to SIMPADU user satisfaction Universitas Negeri Makassar within Faculty of Languages and Literature in Business English study program active in odd semester 2014/2015. This study also proves that simultaneously or together - Reliability, Ease of use, flexibility, and functionality have significant effect on SIMPADU user satisfaction.